APPLICATION OF SIAM WEED COMPOST FERTILIZER AND IRRIGATION FREQUENCY ON GROWTH AND YIELD OF SHALLOTS (Allium ascalonicum L.) - Najwa Raya Azzahra; Darban Haryanto; Ellen Rosyelina Sasmita; Heti Herastuti (Jurnal Agrivet, 2026)
Shallots are a horticultural commodity with high market demand, appropriate cultivation practices are required to increase productivity. Fertilization and irrigation are important for shallot cultivation. This study aimed to determine the interaction and most effective treatment between Siam weed compost dosage and irrigation frequency on the growth and yield of shallots. The experiment used a Completely Randomized Design (CRD) with two factors and one control. The first factor was Siam weed compost at doses of 10, 20, and 30 tons/ha. The second factor was irrigation frequency once per day, twice per day, and once every two days. ANOVA at 5% level was used to analyze the data, followed by DMRT for post hoc comparison at 5%. Differences between the control and treatment combinations were tested using orthogonal contrasts at the 5% level. The results showed an interaction between Siam weed compost and irrigation frequency. A compost dose of 30 tons/ha produced the highest root weight and volume, while irrigation twice per day improved root weight and volume. The treatment combinations differed significantly from the control in plant height at 4, 6, and 8 WAP, fresh and dry bulb weight per plant, bulb yield per plot and hectare, and harvest index.